IMPLEMENTASI TATA KELOLA ADMINISTRASI UNTUK MEWUJUDKAN PELAYANAN PUBLIK YANG BERKUALITAS DI DINAS PENDIDIKAN KOTA MATARAM - Ida Ayu Suci Padmawati; Khairul Imam; Naufal Ikhsanul Jabbar; Angga Mulyadin; Neyna Deasy Lestari; Melda Syahrina; Muh. Zubair (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is motivated by the importance of administrative governance in supporting the improvement of public service quality, particularly in government institutions in the education sector. The problem addressed in this study concerns how the implementation of administrative governance at the Department of Education of Mataram City contributes to achieving high-quality public services. The study aims to describe the implementation of administrative governance and to identify supporting and inhibiting factors in public service processes. The method used is a descriptive qualitative approach with data collection techniques including in-depth interviews, observation, and documentation. The data were analyzed through data reduction, data display, and conclusion drawing. The results show that administrative governance at the Department of Education of Mataram City has been implemented fairly well through the management of correspondence, document archiving, education data management, and other administrative services conducted in accordance with standard operating procedures (SOP). The implementation of administration is supported by clear task distribution, structured service procedures, utilization of information technology, and well-organized records management, resulting in more effective and efficient services. In addition, supporting factors include human resource competence, a conducive work environment, organizational policies, and the implementation of Minimum Service Standards (MSS). However, several constraints are still found, such as mismatches in employee competencies, limited infrastructure, and suboptimal work discipline. Therefore, administrative governance plays an important role in improving public service quality at the Department of Education of Mataram City.